An enigmatic species of Croton (Euphorbiaceae) is rediscovered after more than 100 years in midwestern Brazil - Silva, Marcos J. Da; Sodré, Rodolfo Carneiro; Berry, Paul E. (Phytotaxa, 2015)
Croton spica, an enigmatic species of Croton, was newly recollected after more than 100 years and is herein redescribed, including fruits and seeds, and illustrated for the first time. The species was described by Henri Baillon in 1864 and is part of a complex of similar species that includes C. abaitensis, C. agoensis, C. longinervius, C. mucronifolius and C. pycnadenius, all of which occur predominantly in the Brazilian Planalto. A detailed description, illustration, photographs, distribution, habitat, phenology, IUCN Red List Category, morphological relationships, and a key to Croton spica and allied species are provided.